Future Aspects of Tumor Suppressor Gene - Cheng, Yue (IntechOpen, 2013)
Tumor suppressor genes (TSGs) and their signaling networks are fast growing areas in current biomedical science. These groups of genes, which are not limited to tumor suppression, play critical roles in many cellular activities. This book, "Future Aspects of Tumor Suppressor Genes", contains some fascinating fields, from basic to translational researches, in recent TSG studies. For example, several TSG signaling pathways are addressed in this book, and both mouse and Drosophila models used for the exploration of these genes are described based on the experimental evidence. A detailed review for current knowledge of microRNA studies in the regulation of tumor growth is introduced. Additionally, how natural compounds interfere with the progression of cancer development via TSG pathways is systemically summarized. Recent progresses in cell reprogramming and stemness transition processes regulated by TSG pathways are also included in this book.